Are French Fries and Grades Bad for You? Conflicting Evidence on how K-12 Teachers Search in a K-12 Engineering Digital Library - Reitsma,Reindert; Klenk,P.; Zarske,M.; Sullivan,J. (Am. Soc. of Engr. Education (ASEE) Annual Conf. 2010, 2010)
The TeachEngineering digital library provides teacher-tested, standards-based engineering content for K-12 teachers to use in science and math classrooms. Since its release in 2005, it has demonstrated significant growth in users and in contributors; data on this growth is presented. The TeachEngineering team continues to research its search functions and user interface in order to ensure that it is meeting the needs of its intended users, K-12 teachers. Empirical evidence of an experimental study on the dimensions of alignment between digital K-12 lesson materials and education standards, however, contradicts that of the observed search behavior of patrons of TeachEngineering. Whereas the experiment convincingly shows that grade band information does not add to the teaching materials’ relevance for an educational standard, observed patrons’ searching patterns show ample evidence of grade band-based searches. In this paper we offer that although grade band-based searches should perhaps be avoided because they improperly bias search results, they are such a prominent feature in the actual use of the digital library that as designers we must support them while mitigating the risk of unfortunate search bias. As a possible solution we suggest supporting grade-based searches yet offering query expansion by widening the grade band. These results also imply that curriculum developers pay close attention to the assignment of grade bands to their lessons and activities.
Keywords: BIS